Pharmacogenomic or ‐epigenomic biomarkers in drug treatment: Two sides of the same medal?. Issue 5 (29th March 2016) - Ingelman‐Sundberg, M; Cascorbi, I
Abstract : Interindividual differences in expression of ADME genes are controlled by both genetic and epigenetic factors. Much emphasis has been made to describe the genetic influence, whereas the epigenetic part is not fully understood. Currently, we utilize mainly genetic biomarkers for optimization of drug therapy, although many rare genetic variants are not taken into consideration. Now, also epigenomic biomarkers are at hand and together genetic and epigenetic biomarkers can indeed improve the predictability of drug treatment.